Transforming Science Education: The Effect of Immersive Technology on Student Performance - Ani Susanti; Awanis Hidayati; Hendra Wijaya; Novaria Nusantara; Arie Susanty; Fazhar Restu Fauzi (Southeast Asian Journal on Open and Distance Learning, 2024)
This study examines the influence of immersive technology on student learning outcomes, emphasising its efficacy in improving comprehension of intricate scientific ideas, particularly the solar system. A quasi-experimental approach was utilised, featuring an experimental group utilising immersive technology tools and a control group receiving conventional video-based teaching. Data were gathered via pre-tests and post-tests to evaluate knowledge acquisition, in addition to observations and questionnaires to measure student involvement and participation. The results revealed significant improvements in both groups, with the control group achieving higher post-test scores, potentially due to the familiarity and structured nature of the traditional methods. However, the experimental group demonstrated the unique benefits of immersive technology, particularly in visualizing abstract concepts and fostering interactive learning experiences. These findings suggest that while immersive technology has substantial potential, its effectiveness depends on the context and implementation. Future research should explore its long-term impact and strategies for optimizing its integration into diverse educational settings